2016
DOI: 10.1097/dss.0000000000000756
|View full text |Cite
|
Sign up to set email alerts
|

Direct Cost-Analysis of Mohs Micrographic Surgery and Traditional Excision for Basal Cell Carcinoma at Initial Margin Clearance

Abstract: On average, MMS was found to be $40.96 more expensive than TE in treating BCC-a small but appreciable difference. This being the case, any fiscal comparison must also be tempered with a consideration of effectiveness. Accordingly, further work in the form of a cost-utility study is required to truly define the cost-effectiveness of MMS compared with TE in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Compared with surgical excision, total treatment costs of MMS seem to be higher, but the debate is still ongoing due to the higher recurrence rate of traditional excision 4,7,8,21,26‐28 . In the European experience, differing health systems make it difficult to obtain a specific estimate of the economic weight of these procedures 26,29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with surgical excision, total treatment costs of MMS seem to be higher, but the debate is still ongoing due to the higher recurrence rate of traditional excision 4,7,8,21,26‐28 . In the European experience, differing health systems make it difficult to obtain a specific estimate of the economic weight of these procedures 26,29 .…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, relapsed BCCs were treated again with MMS and are currently Compared with surgical excision, total treatment costs of MMS seem to be higher, but the debate is still ongoing due to the higher recurrence rate of traditional excision. 4,7,8,21,[26][27][28] In the European experience, differing health systems make it difficult to obtain a specific estimate of the economic weight of these procedures. 26,29 This lack of clarity on the costs of MMS and the complex management strategy may explain the low application of the technique in many countries, including Italy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the costs of CE and MMS are substantially less. Not including the cost of pathology, the costs of MMS and CE for BCC have been reported s roughly $600 to $1000 and $600 to $750, respectively, for truncal lesions …”
Section: Discussionmentioning
confidence: 99%
“…SE AU $628.47 vs. AU$587.51). 38 In the SE group, 37.8% would have had incomplete margins and were assumed to require further SE.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…An Australian study (2–3 mm for standard margin and 3–4 mm for high‐risk tumours) on head and neck BCC ( n = 397, 309 pBCC) showed that overall cost difference was AU$40.96 ( P < 0.01) more expensive for MMS (mean cost of MMS vs. SE AU$628.47 vs. AU$587.51) 38 . In the SE group, 37.8% would have had incomplete margins and were assumed to require further SE.…”
Section: Data Analysedmentioning
confidence: 99%